2022
DOI: 10.1155/2022/8604322
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pulse Indicator Continuous Cardiac Output Monitoring on Septic Shock Patients: A Meta-Analysis

Abstract: Background. Septic shock (SS) is the most common severe syndrome in the Intensive Care Unit (ICU). Enhancing the monitoring of hemodynamic indexes in SS patients carries huge clinical implications for reducing patient mortality. Recently, pulse indicator continuous cardiac output (PICCO) has been widely used in clinical practice, but its advantages than central venous pressure (CVP) in guiding the treatment of SS patients remains to be refined. Therefore, this study is aimed at assessing the clinical effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…A recent meta-analysis included 10 studies comparing during septic shock management by TPTD rather than by monitoring alone of CVP. It showed that using TPTD reduced day-28 mortality and the duration of mechanical ventilation, with no difference in the volume of resuscitation fluid [42]. Nevertheless, this result is based on small studies with major methodological limitations.…”
Section: Does Advanced Monitoring Improve the Prognosis Of Critically...mentioning
confidence: 87%
“…A recent meta-analysis included 10 studies comparing during septic shock management by TPTD rather than by monitoring alone of CVP. It showed that using TPTD reduced day-28 mortality and the duration of mechanical ventilation, with no difference in the volume of resuscitation fluid [42]. Nevertheless, this result is based on small studies with major methodological limitations.…”
Section: Does Advanced Monitoring Improve the Prognosis Of Critically...mentioning
confidence: 87%
“…Previous meta-analysis has shown that PiCCO can improve the prognosis of patients with septic shock. Septic shock is closely related to ARDS 31 . Therefore, we believe that patients with ARDS may also bene t from PiCCO monitoring technology.…”
Section: Discussionmentioning
confidence: 99%
“…International guidelines for management of sepsis and septic shock 2021 suggests that aggressive uid resuscitation should be administered to patients with septic shock as soon as possible, but the subsequent infusion of uid required for intravenous administration can cause uid overload 36 . Therefore, PiCCO may improve the effect of uid resuscitation in patients with sepsis/septic shock with the reason that it can guide uid management through dynamic assessment of volume status in order to avoid uid overload while maintaining effective tissue perfusion 31 .…”
Section: Discussionmentioning
confidence: 99%